Faktor-faktor Pemenangan Anggota Legislatif Perempuan Fraksi PKB dan PDI-Perjuangan pada Pemilu Tahun 2014 di Kabupaten Pekalongan - Wahyu Kurniawan; Dzunuwanus Ghulam Manar (Journal of Politic and Government Studies, 2018)
The representative of Woman is regulated in every election process stages settled in the Law. Where the quota regulates party organizing and legislative candidacy. The Party is required to comply with these rules in order to become an election participant. Moreover, the party is also required to be able to nominate the best cadres to be able to compete with other candidates. The party has a right to vote for those to be nominated in order to increase the party's vote. In addition to parties that compete in the election, each candidate of course also compete with other candidates to get support from the community including women candidates. The purpose of this paper is to know what are the factors to influence in the winning of women legislative members from PKB and PDIP fractions in the 2014 Election in Pekalongan Regency reminding the votes of both parties are consistent from the 2009 General Election and 2014 Election.The theory used in this research is the Political Marketing theory used to be able to know the strategies used by each elected female candidate. In Political Marketing theory there are 4 aspects namely Product, Promotion, Price, and Place. The research is done by qualitative research method. The data collection is done by through in-depth interviews with source persons and field documentation.The results of research that done are in the vote acquisition each candidate have its own factor. The factors used in the winning of female legislative members from PKB and PDI-Perjuangan fractions in the 2014 Election in Pekalongan Regency are political parties, candidate figures, successful teams, and families. Each of these factors has its own role in accordance with the needs of the candidate. The strategy used through Political Marketing theories are Product, Promotion, Price, and Place. The product is the vision and the mission that is offered to the community. The mission vision is about sustainable development for the improvement of the people's economy. Promotion is the strategy used by each candidate. The strategy used is to go directly to all levels of society. Price is a range to know the cost required of each candidate. For the price of one seat a legislative member is very expensive given the intense competition. Places are used for mapping territories and approaching communities regarding language use for campaigns. Because of the women election become legislative members, it is expected to give spirit and motivation for society especially women to be brave of politics because politics not only belong to men but also women can compete even their achievement can be more than men.Keywords: political party, female candidate, winner